Satisfaction of sports services users in Orihuela (Alicante) - J. García Mayor; J. M. Vegara Ferri; G. F. López Sánchez; A. Díaz Suárez (Universidad de Murcia, 2016)
The aim of this study was to evaluate the perceived quality and user satisfaction of the municipal sports facility "Water Palace" in Orihuela (Alicante). The sample was formed by 36 users of the facility. Questionnaire EPOD (Nuviala, Tamayo, Iranzo and Falcón, 2008) was administered to the sample in order to measure the users satisfaction. The most significant results show that users are satisfied with the sports facility, with the best results in the image of the organization, the activities and technical aspects. The lowest scores appear in sports facilities and material. Therefore, it is concluded that, as future implications in the management of the facility, it is advisable to focus the attention on the dimensions related to sports facilities and material because they obtained the lowest scores.